Two-Dimensional Speckle Tracking Echocardiography Detects Subclinical Left Ventricular Systolic Dysfunction among Adult Survivors of Childhood, Adolescent, and Young Adult Cancer. (28th January 2016) - Yu, Anthony F.; Raikhelkar, Jayant; Zabor, Emily C.; Tonorezos, Emily S.; Moskowitz, Chaya S.; Adsuar, Roberto; Mara, Elton; Huie, Kevin; Oeffinger, Kevin C.; Steingart, Richard M.; Liu, Jennifer E.
Abstract : Two-dimensional speckle tracking echocardiography (2DSTE) provides a sensitive measure of left ventricular (LV) systolic function and may aid in the diagnosis of cardiotoxicity. 2DSTE was performed in a cross-sectional study of 134 patients (mean age: 31.4 ± 8.8 years; 55% male; mean time since diagnosis: 15.4 ± 9.4 years) previously treated with anthracyclines (mean cumulative dose: 320 ± 124  mg/m 2 ), with (n = 52 ) or without (n = 82 ) mediastinal radiotherapy. The prevalence of LV systolic dysfunction, defined as fractional shortening < 27%, LV ejection fraction (LVEF) < 55%, and global longitudinal strain (GLS) ≤ 16%, was 5.2%, 6.0%, and 23.1%, respectively. Abnormal GLS was observed in 24 (18%) patients despite a normal LVEF. Indices of LV systolic function were similar regardless of anthracycline dose. However, GLS was worse (18.0 versus 19.0, p = 0.003 ) and prevalence of abnormal GLS was higher (36.5% versus 14.6%, p = 0.004 ) in patients treated with mediastinal radiotherapy. Mediastinal radiotherapy was associated with reduced GLS (p = 0.040 ) after adjusting for sex, age, and cumulative anthracycline dose. In adult survivors of childhood, adolescent, and young adult cancer, 2DSTE frequently detects LV systolic dysfunction despite a normal LVEF and may be useful for the long-term cardiac surveillance of adult cancer survivors.